Test–retest reliability of skeletal muscle oxygenation measurement using near‐infrared spectroscopy during exercise in patients with sport‐related iliac artery flow limitation. (25th January 2022) - van Hooff, Martijn; Meijer, Eduard J.; Scheltinga, Marc R. M.; Savelberg, Hans H. C. M.; Schep, Goof
Abstract: The ankle‐brachial index is an accurate tool for detecting claudication in atherosclerotic patients. However, this technique fails to identify subtle flow limitations of the iliac arteries (FLIA) in endurance athletes. Near‐infrared spectroscopy (NIRS) is a noninvasive technique that measures skeletal muscle tissue oxygenation status. The aim of the present study is to examine the absolute and relative test–retest reliability of NIRS and evaluate its potential as a diagnostic tool in FLIA. NIRS‐derived exercise variables were analyzed during exercise and recovery in FLIA 17 patients and 19 healthy controls. The relative reliability of absolute variables (such as the maximal value) were slight to yet predominantly substantial (intraclass correlation coefficient [ICC], ICC range: 0.06–0.76) with good to excellent absolute reliability (absolute limits of agreement [ALoA], ALoA range: 0.8 ± 10.2 to 0.7 ± 13.1; coefficient of variation [CV], CV range: 5%–11%). Absolute values encompassing signal amplitudes showed moderate to almost perfect relative reliability (ICC range: 0.51–0.89) and poor to good absolute reliability (ALoA range: −1.3 ± 7.0 to −2.5 ± 15.7; CV range: 15%–32%). Kinetic variables showed moderate to almost perfect relative reliability for most recovery kinetics variables (ICC range: 0.54–0.86) with fair to good absolute reliability (ALoA range: 0.4 ± 12.2 to 3.9 ± 37.9; CV range: 18%–27%). Particularly, kinetic variables showed significant differences between patients and healthy subjects. NIRS is found to be a reliable method for examining muscle tissue oxygenation variables. Given the significant differences in especially recovery kinetics between normal subjects and patients, NIRS may contribute to diagnosing FLIA in endurance athletes.